Search for down-type fourth generation quarks with the ATLAS detector in events with one lepton and hadronically decaying W bosons - Aad, Georges; Anders, Christoph; Anders, Gabriel; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physical review letters, 2012)
This Letter presents a search for pair production of heavy down-type quarks decaying via b′→Wt in the lepton+jets channel, as b′¯b′→W−tW+¯t→b¯bW+W−W+W−→l±νb¯bq¯qq¯qq¯q. In addition to requiring exactly one lepton, large missing transverse momentum, and at least six jets, the invariant mass of nearby jet pairs is used to identify high transverse momentum W bosons. In data corresponding to an integrated luminosity of 1.04 fb−1 from pp collisions at √s=7 TeV recorded with the ATLAS detector, a heavy down-type quark with mass less than 480 GeV can be excluded at the 95% confidence level.
G. Aad, C.F. Anders, G. Anders, V. Andrei, Y. Davygora, T.A. Dietzsch, C. Geweniger, P. Hanke, M. Henke, G. Kasieczka, A. Khomich, E.E. Kluge, A. Kugel, V. Lendermann, R. Maenner, K. Meier, F. Müller, R. Narayan, S. Poddar, S. Schaetzel, V. Scharf, S. Schmitt, A. Schöning, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und weitere]
Gesehen am 28.11.2018